Effect of Cerium Oxide Nanoparticles as an Additive in Cryopreservation of Gir Bull Spermatozoa - Z Solanki, Jayesh; B Vala, Karshan; R Ram, Dilip; B Odedara, Arjun; K Chaudhary, Jignesh; J Devmurari, Yash (Indian Journal of Veterinary Sciences and Biotechnology, 2025)
The present investigation was carried out on semen of four Gir bulls at Cattle Breeding Farm, Junagadh for a period of 6 months (Feb July 2024). Semen (n=16 ejaculates) was collected using artificial vagina (Danish model) once weekly from each bull. The semen was  evaluated for sperm quality attributes along with oxidative stress parameters at post-thaw stage of cryopreservation using different  concentrations of Cerium Oxide Nanoparticles, viz., 25 µg/mL, 50 µg/mL, 75 µg/mL CeO2NPs and a control AndroMed® extender.  AndroMed® extender with 75 µg/mL CeO2NPs concentration had significantly (p
Keywords: Cerium oxide nanoparticles; Gir bull; Malondialdehyde; Post-thaw sperm quality; Total antioxidant